The Analysis of Sentences, Utterances, and Presuppositions in The Novel The Little Prince By Antoine De Saint-Exupéry - Ikrimah Nur Azizah; Nabiilah Sahda2; Rahmananda Nur Janati Balqis; Tri Winarti (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This research examines semantic and pragmatic considerations in analyzing sentences, utterances, and presumptions in The Little Prince by Antoine de Saint-Exupéry. The study employs a qualitative descriptive approach, using the models developed by Kreidler (2002) and Yule (1996) to methodically find and classify different linguistic components in the novel. Deliberately chosen passages were used to represent a wide range of language use. The study demonstrates how various sentence types, utterances, and presuppositions work together subtly to enhance the novel's thematic richness and narrative framework. The results emphasize the significance of linguistic analysis in revealing the layers of meaning embedded in literary works, enhancing our understanding of semantics and pragmatics in literary discourse.